Between prescribed work and real work: compensatory hyper acting as an expansive role of intervening professionals of the Familias program in Chile - Arévalo-Vargas, Patricia (Prospectiva. Revista de Trabajo Social e Intervención Social, 2024)
In this paper, I present some of the research findings on the agency's role in the social intervention of the Familias program, a state initiative aimed at overcoming poverty in Chile. Guided by the principles of the grounded theory method, I present results from semi-structured interviews carried out with professionals of social science regarding the social intervention they develop.Between methodological tensions, the characteristic bureaucracy of the state measure, and the distance between prescribed work and actual work, the role of professionals seems to be fundamental for the expansion of individual capacities and neoliberal strategy for overcoming poverty. In this sense, I maintain that professionals of the Families program embody compensatory hyper actors; a concept inspired by studies on individuals and agencies developed in Chile in recent years